The Effect of Training on Improving Knowledge, Attitudes and Practices of Health Cadres about IVA ExaminationThe Effect of Training on Improving Knowledge, Attitudes and Practices of Health Cadres about IVA Examination - Asma' Nurbaiti; Intan Nugraheni Hasanah; Sri Sumarni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Based on Health Profile data, Indonesia could not reach the IVA (Inspeksi Visual Asam asetat) coverage and still experiencing fluctuating conditions from 2016-2018 (Health Ministry of Republic Indonesia, 2018). Prelimenary study result showed that from 10 mothers of health cadres of Puskesmas Singorojo 2 who were interviewed randomly, 70% of mothers had less knowledge, 80% have negative attitude and 80% of mothers had never been socialization about previous IVA examinations. The purpose of this study was determine the effect of training to increase the knowledge, attitudes and practice of health cadres about IVA examination in the Puskesmas Singorojo 02 in district Kendal. This research uses quasy experimental design with one group pre-test and post-test design. Selected research sample using total sampling techniques of 36 respondent. Analysis of data using statistic test of wilcoxon signed ranks. The result showed that with the training had an influence on increasing the knowledge of respondent (p-value = 0.001 and Z = -4,891), improved attitudes of respondents (p-value = 0.001 and Z = -4,753) and increased socialization practices of respondents (p-value = 0.001 and Z = -5.097). The conclusion of this study is the influence of training to increase the knowledge, attitudes and socialization practices of respondents about the IVA examination. This research is expected the clinic to conduct to refresh information to health cadres once a month.